Acute cardiorenal dysfunctions induced by isoprenaline in Wistar rats: Mitigating potential of Juglans regia hull extract - Pawan Kumar Verma; Priyanka Sharma; Shilpa Sood; Sheen Tukra; Nrip K. Pankaj; Gholamreza Abdi; Zuhaib F. Bhat (Food Chemistry Advances)
The present study aimed to determine the attenuating properties of Juglans regia hull extract (JRHE) in mitigating isoprenaline (ISO) induced cardiorenal dysfunctions in Wistar rats. Thirty adult Wistar rats were randomly allocated to five groups with six animals in each group. Group I served as control; group II animals were administered ISO and group III received JRHE alone whereas group IV and V received JRHE and quercetin along with ISO, respectively. Administration of ISO in rats induced cardiac and renal tissue damage as reflected by significantly (p < 0.05) increased plasma activities of creatine kinase-myocardial band, lactate dehydrogenase, acetylcholinesterase, arylesterase, blood urea nitrogen, creatinine along with altered antioxidant biomarkers viz. total antioxidant status, total thiols, superoxide dismutase, catalase, glutathione reductase, glutathione peroxidase and increased (p < 0.05) lipid and protein peroxidation in cardiac and renal tissues. Histopathological findings corroborated that ISO has inflicted significant damage on cardiac and renal tissues. Repeated administration of JRHE significantly (p < 0.05) reduced the severity of ISO-induced alterations in blood, cardiac and renal biomarkers. In addition to restoring the levels of altered cardio-renal antioxidant enzymes, JRHE also ameliorated histopathological lesions in cardiac and renal tissues in ISO-treated rats.